Empowering Low-Carbon Behavior through Sustainable Leadership and Green Intellectual Capital in Indonesia’s Public Administration - Halim, M.; Siswanti, Yuni; Amrina, Dania Hellin; Nisa, Risya Khaerun (RSF Conference Series: Business, Management and Social Sciences, 2025)
Governments worldwide face increasing pressure to reduce carbon emissions and align with global climate commitments. Civil servants in Indonesia play a crucial role in implementing policies that advance low-carbon development. While sustainable leadership (SL) is considered essential in shaping pro-environmental behavior, the pathways through which leadership influences employee low-carbon behavior (LCB) remain underexplored. This study examines the mediating role of green intellectual capital (GIC) in the relationship between SL and LCB. A quantitative survey was conducted with 348 civil servants (ASN) across ministries, local governments, and public agencies in Indonesia. Data were analyzed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 4. Robustness checks were performed to address common method bias, non-response bias, and endogeneity. The results reveal that SL does not directly influence LCB; instead, its effect is fully mediated by GIC. This indicates that leadership contributes to carbon-reducing behaviors primarily by building organizational knowledge, skills, and systems that support sustainability. The study extends the resource-based view by showing how SL enhances organizational resources, which in turn drive employee behavior. Practically, the findings highlight the importance of leadership development and green knowledge management as policy levers for achieving Indonesia’s net-zero goals.